2019
DOI: 10.1038/s41533-019-0157-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences among Swedish COPD patients: results from the ARCTIC, a real-world retrospective cohort study

Abstract: The present study aimed to generate real-world evidence regarding gender differences among chronic obstructive pulmonary disease (COPD) patients, especially as regards the diagnosis and outcomes in order to identify areas for improvement and management and optimize the associated healthcare resource allocation. ARCTIC is a large, real-world, retrospective cohort study conducted in Swedish COPD patients and a matched reference population from 52 primary care centers in 2000-2014. The incidence of COPD, prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 37 publications
8
35
1
Order By: Relevance
“…Indeed, it has been reported that biomass smoke-related COPD is associated with milder emphysema and DL CO reduction than tobacco-related COPD [ 48 ]. Our results are similar to recent reports of higher COPD exacerbation frequency among women [ 49 , 50 ], which may reflect the higher hyperresponsiveness prevalence reported in females [ 51 ]. Further, exposure to household biomass smoke pollutants, such as PM 2.5 and NO 2 , have been associated with increased risk of COPD exacerbations [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, it has been reported that biomass smoke-related COPD is associated with milder emphysema and DL CO reduction than tobacco-related COPD [ 48 ]. Our results are similar to recent reports of higher COPD exacerbation frequency among women [ 49 , 50 ], which may reflect the higher hyperresponsiveness prevalence reported in females [ 51 ]. Further, exposure to household biomass smoke pollutants, such as PM 2.5 and NO 2 , have been associated with increased risk of COPD exacerbations [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…There is very limited information on gender differences in COPD management in a primary setting. For example, a recently published study in Sweden described comorbidities and healthcare utilisation among males and females with COPD, as well the frequency of hospitalisation, which were generally similar to the present study [25]. However, there was no information on the QOC in terms of adherence to COPD therapy, administrations of vaccinations and use of spirometry tests.…”
Section: Discussionsupporting
confidence: 81%
“…A recent epidemiological study demonstrated that COPD is now equally prevalent among men and women in Sweden [21]. Furthermore, there has been a lot of information and focus on physicians' education regarding COPD in Sweden in recent years, and the effects of it can be observed in the results of our study.…”
Section: Discussionsupporting
confidence: 61%